An Exploratory Study - Critical Laser Processing of Composite Materials - Sivarao, Subramonian; Sivakumar, Dhar Malingam; Taufik, -; Yuhazri, Yaakob; Tan, CheeFai; Haeryip , Sihombing (2012)
This paper reports an exploratory study of the laser composite cutting process. The laser cutting of composite is a multi-factor process and correct combination of the parameters is needed to achieve high quality and optimum process efficiency. Laser machining based non-contact type advanced machining process with several advantages such as no tool wear, fast, precise and virtually force-free manufacturing method. Laser cutting involves thermal energy process and it does not depend on the strength and hardness of the work piece. In recent years the researchers have explored a number of ways to improve the cut quality of composite materials in different type of lasers. In this paper, an exploratory study is done on critical laser processing of composite materials optimization by other researches which made from available data especially from Science Direct Journal Database. This study predominantly focuses to investigate the correlation between laser machining parameter with the responses. The paper also highlights the experimental control parameters of composite laser machining with responses.